2005
DOI: 10.1002/chin.200549192
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Syntheses of Rolliniastatin 1, Rollimembrin, and Membranacin.

Abstract: All reactions were performed under argon atmosphere. 1 H and 13 C NMR spectra were measured on 300 MHz, 400 MHz and 500 MHz spectrometers. Chemical shift values were recorded in parts per million using the residual undeuterated solvents as internal references and coupling constants in hertz. Infrared spectra (IR) were recorded on a FT-IR spectrophotometer and frequencies are given in reciprocal centimeters. Mass spectra (MS and HRMS) were recorded using chemical ionization (CI), electron impact (EI), or fast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Because substantial amounts of pure samples are required for further biological and clinical studies, a number of total syntheses of AGEs have been reported in the literature since the 1990s. Recent advances in the total syntheses of AGEs include mono-THF AGEs: murisolin (26) [90,91], longicin (27) [92,93], and cis-solamin (28) [94,95], adjacent bis-THF AGEs: bullatacin (14) [96], rolliniastatin 1 (7) [23,97], rollimembrin (29) [97,98], 10-hydroxyasimicin (30) [99,100], membranacin (31) [97,101], asimicin (15) [76,102], longimicin D (32) [103][104], and mucoxin (33) [105,106], non-adjacent bis-THF AGEs: cis-sylvaticin (34) [107,108] and gigantecin (9) [109,110], and others, jimenezin (35) [111,112], mucocin (36) [113,114], pyranicin (37) [115,116], pyragonicin (38) [115,117,118], rollicosin (18) [62,…”
mentioning
confidence: 99%
“…Because substantial amounts of pure samples are required for further biological and clinical studies, a number of total syntheses of AGEs have been reported in the literature since the 1990s. Recent advances in the total syntheses of AGEs include mono-THF AGEs: murisolin (26) [90,91], longicin (27) [92,93], and cis-solamin (28) [94,95], adjacent bis-THF AGEs: bullatacin (14) [96], rolliniastatin 1 (7) [23,97], rollimembrin (29) [97,98], 10-hydroxyasimicin (30) [99,100], membranacin (31) [97,101], asimicin (15) [76,102], longimicin D (32) [103][104], and mucoxin (33) [105,106], non-adjacent bis-THF AGEs: cis-sylvaticin (34) [107,108] and gigantecin (9) [109,110], and others, jimenezin (35) [111,112], mucocin (36) [113,114], pyranicin (37) [115,116], pyragonicin (38) [115,117,118], rollicosin (18) [62,…”
mentioning
confidence: 99%